INTERNATIONAL BIBLIOLOGICAL CONFERENCES THROUGH THE PERSPECTIVE OF SCIENTIFIC COMMUNICATION - BLIŪDŽIUVIENĖ, NIJOLĖ (Knygotyra, 2012)
The article focuses on the experience of Lithuania in international bibliological conferences organized by the Department of Book Science at the Faculty of Communication of Vilnius University in the light of research and knowledge. The analysis of geographical and thematic coverage as well as of organizational issues shows that these conferences have their specific characteristics and can be treated as a phenomenon of scientific and social communication.
Keywords: ...